2004
DOI: 10.1210/jc.2003-031641
|View full text |Cite
|
Sign up to set email alerts
|

Major Genetic Influence on the Regulation of the Pituitary-Thyroid Axis: A Study of Healthy Danish Twins

Abstract: Intraindividual variation is smaller than the interindividual variation in serum TSH, free T(4), and free T(3) concentrations. This suggests that each individual may have a genetically determined thyroid function set-point. A representative sample of self-reported healthy twin pairs was identified through the Danish Twin Registry. A total of 284 monozygotic (MZ), 286 dizygotic same-sex (DZ), and 120 opposite-sex (OS) twin pairs were investigated. A classical twin study was performed. After adjustment for age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
159
1
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(183 citation statements)
references
References 37 publications
9
159
1
10
Order By: Relevance
“…The intra-individual variation of thyroid function tests has been studied in individuals with normal thyroid function (28)(29)(30)(31)(32)(33)(34)(35)(36)(37). This has revealed both a considerable circadian rhythm and a small seasonal variation in TSH secretion, but over time TSH in an individual varies within a range of only half of a population-based reference range.…”
Section: Intra-individual Variation In Thyroid Function Testsmentioning
confidence: 99%
“…The intra-individual variation of thyroid function tests has been studied in individuals with normal thyroid function (28)(29)(30)(31)(32)(33)(34)(35)(36)(37). This has revealed both a considerable circadian rhythm and a small seasonal variation in TSH secretion, but over time TSH in an individual varies within a range of only half of a population-based reference range.…”
Section: Intra-individual Variation In Thyroid Function Testsmentioning
confidence: 99%
“…Previous twin studies confirmed the heritability of thyroid hormone levels (plasma TSH: 64%, fT4: 65% and fT3: 64%) too (23,24) and demonstrated that besides age, BMI, iodine intake, serum TSH concentration, parity and cigarette smoking played a small role in the thyroid size. Genetic loci associated with clinically overt euthyroid multinodular goiter were already mapped in linkage analyses, genome-wide association studies identified four genetic loci associated with thyroid volume and goiter risk (25).…”
Section: Discussionmentioning
confidence: 78%
“…In our study, no pregnant women participated, and thyroid hormone levels were not assessed. However, since thyroid hormone levels are heritable (23), large modifiable effect on our hereditary results (no heritability of thyroid lobe volumes) is not anticipatory. Iodine status did not seem to exert a significant influence on the changes in thyroid volume in a recent study, but changes in BMI levels seemed to be more important (27).…”
Section: Heritability Of Thyroid Volumementioning
confidence: 83%
See 1 more Smart Citation
“…However, the fact that thyroid function appears to be sensitive to selenium supplementation adds to the incentive for investigating its effects on multifactorially regulated traits, such as thyroid function (19,41), size (42,43), and autoimmunity (44) in autoimmune thyroid diseases, where selenoprotein biosynthesis may be impaired (18). A number of trials in Hashimoto's thyroiditis have thus far not clarified the role of selenium supplementation (39).…”
Section: Discussionmentioning
confidence: 99%